From modernity to cosmodernity : science, culture, and spirituality - Nicolescu, Basarab (SUNY series in Western esoteric traditions., 2014)
"Offers a new paradigm of reality, based on the interaction between science, culture, spirituality, religion, and society"--Provided by publisher